Free Water Surface (FWS) System for the Treatment of Domestic Wastewater: A Comparative Study - Özengin, Nihan; Elmaci*, Ayse (Asian Journal of Chemistry, 2014)
In this study, laboratory-scale continuous flow free water surface (FWS) constructed wetland systems were examined for their capacity to remove COD, BOD5, total nitrogen, NH4-N, NO3–, NO2–, total phosphorus and orthophosphate. The floating aquatic plant Lemna minor L. (Duckweed) was used and the system consisted of planted and unplanted reactors. The system was fed with weak and strong synthetic domestic wastewater. In the weak domestic wastewater treatment, the average removal efficiencies obtained from the evaluation of the system were 60.29 and 57.88 % for COD, 16.78 and 11.73 % for BOD, 31.09 and 13.1 % for total nitrogen, 1.92 and 23.2 % for NO3–, 36.61 % and 17.53 % for total phosphorus and 36.4 and 16 % for orthophosphate in planted and unplanted reactors, respectively. The average NH4-N concentration was 0.63 mg L–1 in the influent and 0.92 and 0.62 mg L–1 in the effluent from planted and unplanted reactors, respectively. The average NO2– concentration was 0.51 mg L–1 in the influent and 0.56 and 0.96 mg L–1 in the effluent from planted and unplanted reactors, respectively. In the strong domestic wastewater treatment, the average removal efficiencies obtained from the evaluation of the system were 91.42 and 87.67 % for COD, 79.09 and 69.92 % for BOD, 72 and 63.6 % for total nitrogen, 67.9 and 60.3 % for NH4-N, 0.47 and 33.3 % for NO3–, 98.28 and 98.76 % for NO3–, 66.62 and 54.79 % for total phosphorus and, 61.82 and 51.7 % for orthophosphate in planted and unplanted reactors, respectively. The results showed that this system has a considerable capacity for treating strong domestic wastewater.